Ketersediaan Ruang Terbuka Hijau Publik di Permukiman Kelurahan Sinrijala Kota Makassar - Karlina Karlina; Louis Santoso; Wiwik Wahidah Osman (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2014)
Green open space in urban areas, especially in residential neighborhood, is important to be provided because the increasing of human activities in urban areas encourages the emergence of various environmental issues like vehicle pollution, flooding, decreasing of quality and quantity of groundwater and so forth. This research was conducted to assess the condition and the use of public green open space, to describe the type of public green open space and its existing plants, to identify the provision of green public open space provided at housing and settlement in Sinrijala district. The analytical methods used were descriptive qualitative, quantitative as well as superimpose analysis (overlay technique). The result of this research was the condition and the uses of the existing public green open space in Sinrijala district were not well organized and integrated in the city. Many public green open spaces have not been fully utilized for public interest. The types of public green open space in Sinrijala were public cemetery, green belt of river/canal and green line of road. The allocations of the public green open space in Sinrijala district is 60.66% based on superimpose analysis.